Counseling on fighting germs with a healthy lifestylefor children at a course institution - Riri Safitri (JURNAL PENGMAS KESTRA (JPK), 2026)
Health education initiated at an early age is crucial for raising children's awareness about maintaining their personal health and their environment. Consequently, the author conducted a community service activity in the form of a health education session titled "Fighting Germs through Healthy Living" for children at the Universal Technology Computer course center. The objective was to equip the children with knowledge on how to combat germs by adopting clean and healthy living habits, thereby fostering an awareness of the importance of such behaviors for the future. The activity employed a combination of lectures and hands-on practice. A participatory and interactive approach was used to ensure the material was easily understood and age-appropriate. The target audience consisted of school-aged children who are currently in the stage of developing clean and healthy living habits. There were 16 participants in the session. The activity was carried out in three stages: preparation, implementation, and evaluation. Pre-test results showed that the highest percentage of participants (62.5%) fell into the "low" knowledge category. In contrast, post-test results showed the highest percentage falling into the "high" category, with 68.75% of participants classified as having high knowledge. These findings indicate that the health education session successfully increased participants' knowledge regarding healthy living practices to combat germs. Through the knowledge gained, participants are expected to recognize the importance of adopting clean and healthy living habits. Furthermore, during the hands-on practice session, all participants were able to correctly perform the six-step handwashing procedure and demonstrated enthusiasm and active engagement throughout the activity.